American independent cinema : an introduction - Tzioumakis, Yannis (Edinburgh University Press, 2017)
This introduction to American Independent Cinema offers both a comprehensive industrial and economic history of the sector from the early twentieth century to the present and a study of key individual films, filmmakers and film companies.
Keywords: Independent filmmakers -- United States -- Case studies.; Independent films -- Economic aspects -- United States.; Independent films -- United States -- History and criticism.; Motion picture industry -- United States -- History -- 20th century.; Cinéastes indépendants -- États-Unis -- Études de cas.; Films indépendants -- Aspect économique -- États-Unis.; Films indépendants -- États-Unis -- Histoire et critique.; Cinéma -- Industrie -- États-Unis -- Histoire -- 20e siècle.; PERFORMING ARTS -- Reference.; Independent filmmakers; Independent films; Motion picture industry; United States; 1900-1999; Case studies; Criticism, interpretation, etc.; History